MEMPERKUAT DAYA PEMERINTAHAN GAMPONG PADA MASA PANDEMI COVID-19 DI KABUPATEN ACEH UTARA DAN KOTA LHOKSEUMAWE, ACEH - Teuku Kemal Fasya (Jurnal Transformasi Administrasi, 2020)
This paper entitled “Strenghtening the Village Governmentality during the Covid-19 Pandemic in North Aceh District and Lhokseumawe City, Aceh” discusses village creativity and independence. Qualitative social method is used, with an ethnographic approach; a social research model that emphasizes the inductivity and in-depth aspects of field social research. In practice, the ethnographic approach used is more of a netnographic in nature, because some datas and references were obtained from online and digital information sources. The data in this study were collected through primary sources, namely field observations and in-depth interviews and through secondary sources consisting of document and literature studies to enrich the perspective and scientific concepts of writing. The discussion part of this paper looks at the creativity of the gampong government in Lhokseumawe City and North Aceh District - two identical level II regional governments - in carrying out their roles, especially in implementing Law No. 6 of 2014 concerning the Village. The Covid-19 pandemic has indeed disrupted entire models of government and business, thus affecting the performance of village governance in Aceh. However, some other weaknesses caused by social capital and the impact of past conflicts are also present so that the gampong government has not fulfilled its desire to improve the productive economy of the people as well as good governance capacity. There is an opportunity to revive economic resources at the village level by establishing tourism objects that are environmentally and socially friendly, even though it is still far from the ideal concept of well-established tourism villages such as those found in Yogyakarta, East Java, Bali, West Sumatra, etc.